Serological survey of brucellosis in livestock animals and workers in Ibadan, Nigeria (2006)
A serological survey of brucellosis in livestock animals and workers was conducted in Ibadan, Southwestern Nigeria between May and August 2004. A total of 1,210 cattle, 54 sheep, 496 goats, 200 pigs and 21 humans (i.e. butchers and herdsmen) were screened using the Rose Bengal test (RBT).From the results, prevalence in trade cattle was 5.82% while 0.86% was recorded in goats. None of the sheep and pigs was positive to the test. Out of the 11 samples taken from butchers, seven were positive and none of the ten herdsmen were sero-positive. This gives an infection rate of 63.3% in the butchers; and a combined infection rate of 31.82% in humans. This shows that brucellosis is still a major zoonosis in Nigeria; other public health implications are discussed